The effect of liver test abnormalities on the prognosis of COVID-19 (2020)
Introduction: COVID-19 caused by the SARS-CoV-2 continues to spread rapidly across the world. In our study, we aim to investigate the relationship between the liver enzymes on admission (AST, ALT, ALP, GGT) and severity of COVID-19. We evaluated course of disease, hospital stay, liver damage and mortality. Materials and methods: Our study included 614 patients who were hospitalized with the diagnosis of COVID-19 between 03.16.20 and 05.12.20. Patients with liver disease, hematological and solid organ malignancy with liver metastases were excluded, resulting in 554 patients who met our inclusion criteria. We retrospectively evaluated liver transaminase levels, AST/ALT ratio, cholestatic enzyme levels and R ratio during hospital admission and these were compared in terms of morbidity, mortality and clinical course. Results: Mean age of 554 subjects were 66.21 ± 15.45 years, 328 (59.2%) were men. The mean values of liver enzymes on admission were AST (36.2 ± 33.6 U/L), ALT (34.01 ± 49.34 U/L), ALP (78.8 ± 46.86 U/L), GGT (46.25 ± 60.05 U/L). Mortality rate and need for intensive care unit were statistically significant in subjects that had high ALT–AST levels during their admission to the hospital (p = 0.001). According to the ROC analysis AST/ALT ratio was a good marker of mortality risk (AUC = 0.713: p = 0.001) and expected probability of intensive care unit admission (AUC = 0.636: p = 0.001). R ratio, which was used to evaluate prognosis, showed a poor prognosis rate of 26.5% in the cholestatic injury group, 36.1% in the mixed pattern group and 30% in the hepato-cellular injury group (p 0.001). Conclusions: ALT–AST elevation and AST/ALT ratio >1 was associated with more severe course and increased mortality in COVID-19.